Respuesta :

[tex] \frac{b}{13} [/tex] - [tex] \frac{3b}{13} [/tex] = [tex] \frac{8}{13} [/tex]
Since the two fractions have a common denominator already, we can just subtract the numerators.
b-3b=-2b or -3b+b=-2b
Either way you get the same answer :)
Our new fraction is [tex] \frac{-2b}{13} [/tex]
Now we know that this must be equal to [tex] \frac{8}{13} [/tex]
Again, since the denominators are already the same of course they are equal. 13=13
Now we have to set the numerators equal
-2b=8
Use inverse operations to get b alone
-2b=8
÷-2   ÷-2
b=-4
If you have any questions, feel free to ask. Hope this helped! :)